Pemberdayaan Masyarakat Melalui Kegiatan Rohani dan Sosial di Desa Hutaraja Simanungkalit - Adi Suhenra Sigiro; Debora Retinawati Nababan; Putri Yulia Citra Br. Berutu; Desy Mariana Siringoringo; Berlina Simatupang; Fritcen Vanny M. Pardede; Prianus Mom (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
Community empowerment is an important pillar in social development in Indonesia. This article discusses the implementation of the Merdeka Belajar-Kampus Merdeka (MBKM) Program by students of the Christian Leadership Study Program, Faculty of Theology, Tarutung State Christian Institute in Hutaraja Simanungkalit Village, Sipoholon District, North Tapanuli Regency. This activity focuses on spiritual and social development, through a literacy mentoring program for children and support for the elderly. The research method used is a qualitative descriptive approach with a collaborative participatory method, which allows active interaction between students and the community. Data collection was carried out through observation, informal interviews, and documentation of activities. The evaluation results showed that the program succeeded in improving children's basic literacy skills and providing emotional support for the elderly, as well as strengthening social relationships in the community. Through this experience, students developed social skills and empathy, while the community felt the positive impact of student involvement. This article emphasizes the importance of collaboration between the academic world and local communities in realizing effective and sustainable empowerment.